2020
DOI: 10.1039/d0se00155d
|View full text |Cite
|
Sign up to set email alerts
|

Big problem, little answer: overcoming bed agglomeration and reactor slagging during the gasification of barley straw under continuous operation

Abstract: Leaching barley straw has been found to eliminate reactor slagging and fluidised bed agglomeration under continuous gasification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Fluidization properties: formation of agglomerates or low melting compounds with parts of the feedstock must be avoided. This becomes difficult if a herbaceous feedstock-high in ash and alkali metals-is used and might require mitigation measures like pre-treatment [30,31] or feedstock mixing [32]. 7.…”
Section: Bed Materials For Chemical Looping Gasificationmentioning
confidence: 99%
“…Fluidization properties: formation of agglomerates or low melting compounds with parts of the feedstock must be avoided. This becomes difficult if a herbaceous feedstock-high in ash and alkali metals-is used and might require mitigation measures like pre-treatment [30,31] or feedstock mixing [32]. 7.…”
Section: Bed Materials For Chemical Looping Gasificationmentioning
confidence: 99%
“…Many researchers carried out straw leaching at different temperatures, from 25 up to 100 °C . Consumption of distilled, deionized or tap water for straw leaching was characterized by water-to-straw ratio, which was from (0.00525–0.024) L/g (Thompson et al), 0.012 L/g (Wu et al), 0.040 L/g (Jenkins et al), 0.050 L/g (Ma et al), and up to 0.065 L/g (Alabdrabalameer et al) . Straw leaching was often conducted without control of leaching completion; measurements of leachate electrical conductivity or water consumption were not reported. , …”
Section: Introductionmentioning
confidence: 99%
“…There are different approaches to describing the behavior of leached straw ash: measurements of ash composition with calculations changing slagging and fouling indexes, describing the behavior of leached straw ash in energy installation, and determining characteristic temperatures of ash melting behavior . In the last-mentioned paper, it was shown that due to appropriate water leaching, the ash deformation temperature increased from 920 °C for the original straw to 1320 °C for the leached, and for another sample of straw, from 910 to 1250 °C .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations